評估短時間尺度氣候變遷與化學風化的動態關係( I ) - 劉厚均 (2020)
計畫編號︰MOST109-2636-M006-016 執行機構: 國立成功大學地球科學系（所） 研究期間: 2020-08~2021-07 矽酸鹽礦物的風化已經被認為是在長期時間尺度上調節大氣中二氧化碳濃度的重要機制。由於碳酸鹽相對快速的溶解反應特性，無論在長時間或是短時間尺度上都很容易受到各種氣候或是人為擾動的影響。因此，近年來科學界逐漸意識到碳酸鹽風化對於改變大氣二氧化碳水平的重要性。放射性與穩定鍶同位素系統對於風化的來源（87Sr/86Sr）及風化環境中所發生的生地化作用（δ88/86Sr）相當靈敏；已經被運用在評估海洋鍶的收支模型，進而了解陸源風化作用與氣候變遷之間的關係。然而，目前為止對於短時間尺度下陸源風化作用（特別是碳酸鹽的風化）與氣候變遷（如：溫度與水文狀態）的關聯性仍有待更進一步的釐清。因此，探索在不同時間尺度與氣候條件下，河水化學與同位素組成如何反應不同的風化機制，其靈敏度與可能的變異程度，對於人文社會理解與適應短期全球碳循環與氣候變遷的趨勢有所助益。本研究計畫將致力於釐清：（1）評估流域系統中次生方解石沈澱對於穩定鍶同位素分化的控制機制；（2）釐清在短期氣候變遷下，風化來源變化與發生次生礦物沈澱的動態變化，與其對河水化學與同位素組成的變異程度；（3）評估為人因素可能導致加速碳酸鹽風化的可能性及其對全球碳循環的潛在影響。本研究為五年期的計畫，將循序漸進透過分年計畫來解答上述的科學問題：（1）在國立成功大學發展有別於現階段標準更高精確度的84Sr-87Sr雙示蹤劑（Double Spike）穩定鍶同位素測量方法；（2）透過中國西南白水台鈣華礦床中的鈣滑沉澱評估次生碳酸鈣沈澱時動力學與熱力學效應造成的潛在穩定鍶同位素分化；（3）分別在喜馬拉雅-西藏-青康藏高原地區石灰岩與矽酸鹽流域，模擬與評估不同氣候條件變化下，化學風化作用與次生礦物生成所扮演的角色及對全球碳循環的影響；（4）評估人類活動對於短期風化作用的可能影響；（5）建立以納入考量不同時間尺度下風化來源變化與次生礦物生成動態關係的海洋鍶收支模型。本計畫的成果將有助於我們更深入理解短時間尺度化學風化、全球碳循環與氣候變化之間的關聯性，對於社會所關注未來大氣二氧化碳濃度的變化趨勢及可能通過海洋酸化影響生態系統的憂慮至關重要。 Although the weathering of silicate minerals has been recognized as an essential role in regulating the atmospheric CO2 level at the long-term timescales, the scientific community is gradually realizing the significance of carbonate weathering because its rapid dissolution kinetic sensitive to any kinds of climatic and anthropogenic perturbations at either short-term or long-term timescales. Radiogenic and stable Sr isotopes have recently been used as robust tracers for constraining the marine Sr budget because they are sensitive to weathering source changes (87Sr/86Sr) and post-weathering reactions (δ88/86Sr). However, significant challenges raise from the poor understanding of the sensitivity and variability of the riverine δ88/86Sr responsible for the weathering processes and climate changes, particularly the quick response of carbonate dissolution and precipitation to the short-term climate changing. Therefore, a better understanding of the sensitivity and variability of river water δ88/86Sr and its connections between chemical weathering and climatic parameters will improve our scientific knowledge about the short-term and long-term global carbon cycling and climate change, which is critical to issues of great societal concern. This project will result in 1) an evaluation of mechanisms controlling stable Sr isotope fractionation during secondary calcite precipitation in freshwater systems, 2) deciphering the roles of weathering source changes and secondary mineral precipitation responsible for short-term climate changes under different lithology and weathering intensity conditions, and 3) an examination of anthropogenic influences on possibly accelerating carbonate weathering and their potential implications for global carbon cycles. Accordingly, this project seeks fund to 1) significantly improve the analytical precision of δ88/86Sr determinations by establishing an 84Sr-87Sr double spike methodology at National Cheng Kung University, 2) evaluate the potential kinetic and equilibrium controls on δ88/86Sr fractionation during continental calcite precipitation in a travertine deposit of Baishuitai, Yunnan, SW China, 3) explore the sensitivity of chemical weathering and secondary mineral precipitation to short-term climate change at the drainage systems of the Himalaya-Tibetan-Plateau regions, 4) assess the role of anthropogenic activities on short-term chemical weathering, and 5) assess a new model of marine Sr budget considering the dynamics of weathering source changes and secondary mineral precipitation. The results of this project will enhance our understanding of the linkage between chemical weathering, global carbon cycling, and climate changes, which is critical to issues of great societal concern such as our ability to predict the fate of CO2 in the atmosphere and its impact on the ocean ecosystem through ocean acidification.